The Sacco-Vanzetti case : transcript of the record of the trial of Nicola Sacco and Bartolomeo Vanzetti in the courts of Massachusetts and subsequent proceedings, 1920-7. - Sacco, Nicola, 1891-1927; Vanzetti, Bartolomeo, 1888-1927; Baker, Newton Diehl, 1871-1937 (World trials library., 1928)
Transcript of trial for the murder of Alessandro Berardelli and Frederick Albert Parmenter held in 1921.